2019
DOI: 10.1016/j.bbmt.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Outcomes of Allogeneic Peripheral Blood versus Bone Marrow Hematopoietic Stem Cell Transplantation in Major Thalassemia: A Multivariate Long-Term Cohort Analysis

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) currently is the only available curative option for transfusion-dependent thalassemia. Peripheral blood is a more convenient source for HSCT in comparison with bone marrow. Information about the relative success of transplantation with these 2 graft sources would help physicians and patients choose between them. The aim of this study was to evaluate the pros and cons of using peripheral blood instead of bone marrow as the graft source in thalassemia tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…We speculate that use of peripheral blood stem cells may result in a higher incidence of aGVHD than bone marrow application. Ghavamzadeh et al concluded that peripheral blood stem cell transplantation is associated with higher incidence rates of aGVHD and cGVHD compared with bone marrow utilization, but blood cells are easier to harvest and associated with lower incidence of GR and shorter times to neutrophil and platelet engraftment, resulting in similar OS outcomes to bone marrow transplantation (27).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that use of peripheral blood stem cells may result in a higher incidence of aGVHD than bone marrow application. Ghavamzadeh et al concluded that peripheral blood stem cell transplantation is associated with higher incidence rates of aGVHD and cGVHD compared with bone marrow utilization, but blood cells are easier to harvest and associated with lower incidence of GR and shorter times to neutrophil and platelet engraftment, resulting in similar OS outcomes to bone marrow transplantation (27).…”
Section: Discussionmentioning
confidence: 99%
“…First is the use of G-BM&PBSCs as the graft source in the present study. Ghavamzadeh et al [3] reported that patients receiving PBSCT have a shorter median time for neutrophil and platelet engraftments compared with the patients receiving BMT (3 days and 11 days shorter, respectively), and the GR rate is lower (5.7% versus 18.4%), showing higher incidence of acute GVHD (33.3% versus 50.8%) and chronic GVHD (26.1% versus 51.4%). Zhao et al [5] reported that coinfusion of G-BM&PBSC graft resulted in similar engraftment kinetics and lower rates of grade III-IV acute GVHD compared with PBSC grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The grafts used in the present study were G-BM&PBSC grafts, which were intended to be used to combine the advantages of both elements. PBSCs have more CD34 + cells and T cells than steady-state BM, and they have been shown to accelerate engraftment and decrease GR [3,21]. Morton et al [22] reported that G-BM transplantation leads to reduced severity of acute GVHD and less subsequent chronic GVHD, and engraftment is comparable to that of PBSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Based on current guidelines, allogeneic hematopoietic stem cell transplantation (HSCT) remains the only curative treatment option for eligible TM patients and can improve long-term survival. [5][6][7][8][9] It is reported that more than 90% of patients with thalassemia major survive after HSCT and disease-free survival (DFS) is about 80%. 6 Hepatic brosis is a common complication in transfusion-dependent thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%